Equações diofantinas lineares: uma abordagem para o ensino médio utilizando jogo matemático - Sousa, Elvis Maikon Reges (Universidade Federal Rural do Semi-Árido, 2019)
This work presents the proposal of inserting the content of linear diophantine equations in high school. Such idealization is justified by the fact that this theme shapes several problematic situations in the student's daily life, favoring the development of their logical reasoning and providing them with support and motivation to better understand other associated issues, such as linear systems. This content is observed, almost exclusively, to be taught in higher education, usually in the discipline of number theory. It is known, however, that the concepts that structure these themes also belong to elementary school and are therefore of full access to high school students. The application procedure of the themes was designed so as not to coincide with the model in which the content is seen in the undergraduate course, which would be disproportionate. It also shuns the way teaching is approached in the traditional method to which the students involved are already accustomed. The whole practice was developed from two moments with high school students Francisco Moreira Filho, in the city of Tabuleiro do Norte - CE. The first moment, as an essay, brought together students from various classes of the school. The second, in turn, occurred in the same class as the 3rd grade. At this time, the activities took place in two days. On the first day, students received a list of prior knowledge activities on the mathematical content that would be addressed. Then, the game itself was held, with the reading and discussion of the rules, the dispute between pairs and finally the scoring of the points of the game, and the winning team was elected. On the second day, a new list, now addressing issues regarding gaming and math education. Finally, the mathematical topics related to the playful were worked, culminating the process with the predefined linear Diophantine equations and their resolution method. At this stage of the class it was possible to verify in the students the comprehension of concepts such as divisibility and common divisor maximum, resulting in learning and solving the referred equations. The analysis of this class also revealed the game as an important instrument of connection between the student's interest and the proposed knowledge. Thus, the real feasibility of applying the content of linear diophantine equations to high school students is noted, taking care to avoid mathematical rigor and excessive formalism.
Keywords: Equações diofantinas Lineares; Ensino; Jogo no ensino de Matemática; Linear diophantine equations; Teaching; Math teaching game; CIENCIAS EXATAS E DA TERRA::MATEMATICA